2015
DOI: 10.1002/cmdc.201500437
|View full text |Cite
|
Sign up to set email alerts
|

We Need 2C but Not 2B: Developing Serotonin 2C (5‐HT2C) Receptor Agonists for the Treatment of CNS Disorders

Abstract: The serotonin 2C (5-HT2C) receptor has been identified as a potential drug target for the treatment of a variety of central nervous system (CNS) disorders, such as obesity, substance abuse, and schizophrenia. In this Viewpoint article, recent progress in developing selective 5-HT2C agonists for use in treating these disorders is summarized, including the work of our group. Challenges in this field and the possible future directions are described. Homology modeling as a method to predict the binding modes of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…RNA editing generates at least 14 functionally distinct 5-HTR2C isoforms, any of which could be a potential target for improved therapeutic and side effect profiles [ 90 ]. Moreover, the negligible presence of 5-HTR2C in cardiac and vascular tissues makes these receptors ideal targets for treatment of brain disorders, due to their limited peripheral side effects [ 91 ].…”
Section: Serotonin Receptors (5-htr)mentioning
confidence: 99%
“…RNA editing generates at least 14 functionally distinct 5-HTR2C isoforms, any of which could be a potential target for improved therapeutic and side effect profiles [ 90 ]. Moreover, the negligible presence of 5-HTR2C in cardiac and vascular tissues makes these receptors ideal targets for treatment of brain disorders, due to their limited peripheral side effects [ 91 ].…”
Section: Serotonin Receptors (5-htr)mentioning
confidence: 99%
“…The 5-HT 2C receptor represents a promising drug target for obesity and central nervous system disorders, such as schizophrenia and drug addiction [1e4]. Subtype selectivity is essential for the development of potential 5-HT 2C -targeted therapeutics [5], as drugs with 5-HT 2B agonism may induce potentially life-threatening valvular hypertrophy [6,7], while 5-HT 2A agonists are hallucinogenic [8]. However, it is currently a major challenge to develop agonists that are highly selective for 5-HT 2C over 5-HT 2B and 5-HT 2A due to these subtypes' significant homology at structural, genetic, and functional levels.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies have shown that dopamine is preferred and favored as the first line of medication as it increases the arterial pressure mainly through vasoconstriction having little effect on the cardiac output, stroke volume, and the heart rate [29]. Studies carried out have shown that the use of dopamine increases the stroke volume and heart rate.…”
Section: Discussionmentioning
confidence: 99%